ANALISIS KESEHATAN KOPERASI PEGAWAI NEGERI BALAIKOTA SAMARINDA BERDASARKAN PERATURAN DEPUTI BIDANG KEMENTERIAN KOPERASI DAN USAHA KECIL DAN MENENGAH REPUBLIK INDONESIA NO.06/PER/DEP.6/IV/2016 - Sarwo Eddy Wibowo3, Moh.Nasrullah1, Ivana Nina Esterlin Barus2 (EKONOMIA, 2021)
Moh Nasrullah: Health Analysis of Samarinda City Hall Cooperative Employees Based on Deputy Regulations for the Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No.06 / Per / Dep.6 / IV / 2016The purpose of this study was to analyze the health of Samarinda City Township Cooperatives in 2018 if assessed based on the Deputy Regulation of the Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No.06 / Per / Dep.6 / IV / 2016.Analysis tools used are capital aspects, aspects of productive asset quality, management aspects, efficiency aspects, liquidity aspects, independence and growth aspects, and aspects of cooperative identity. The results of the study concluded from the seven aspects assessed that the health of Samarinda City Hall's Civil Servants Cooperative in 2018 was in the title